Ultra-fast plasmonic back reflectors production for light trapping in thin Si solar cells. (1st November 2018) - Araújo, Andreia; Mendes, Manuel J.; Mateus, Tiago; Costa, João; Nunes, Daniela; Fortunato, Elvira; Águas, Hugo; Martins, Rodrigo
Highlights: New method to form highly reproducible plasmonic surfaces in an fast way by RTA process. Influence of the annealing temperature ramp-up rate on the morphology of the nanoparticles. Formation of arrays of Ag NP via dewetting processes in just ten minutes. Influence of the AZO spacer layers thickness on the resulting LT effects produced by the PBRs. Best performing PBR: 120 nm Ag/100 nm AZO/6 nm Ag NPs/60 nm AZO. μ c-Si:H solar cells show an overall 11% improvement on device efficiency. Abstract: A fast method is presented to fabricate plasmonic light trapping structures in just ten minutes (>5 × faster than the present state of art), with excellent light scattering properties. The structures are composed of silver nanoparticles (Ag NPs) deposited by thermal evaporation and self-assembled using a rapid thermal annealing (RTA) system. The effect of the RTA heating rate on the NPs production reveals to be crucial to the decrease of the annealing process. The Ag NPs are integrated in thin film silicon solar cells to form a plasmonic back reflector (PBR) that causes a diffused light reflectivity in the near-infrared (600–1100 nm wavelength region). In this configuration the thicknesses of the AZO spacer/passivating layers between NPs and rear mirror, and between NPs and silicon layer, play critical roles in the near-field coupling of the reflected light towards the solar cell absorber, which is investigated in this work. The best spacer thicknesses were found to be 100 and 60 nm, respectively, for Ag NPs with preferential sizes of about 200 nm. The microcrystalline silicon (μc-Si:H) solar cells deposited on such improved PBR demonstrate an overall 11% improvement on device efficiency, corresponding to a photocurrent of 24.4 mA/cm 2 and an efficiency of 6.78%, against 21.79 mA/cm 2 and 6.12%, respectively, obtained on flat structures without NPs.